Analysis of Factors Related to the Incident of Chronic Kidney Failure in Hypertension Patients - Making, Maria Agustina; Banhae, Yulianti Kristiani; Nugroho, Febtian C.; Hamu, Antonia; Israfil, Israfil (Indonesian Journal of Global Health Research, 2023)
Chronic kidney failure is a global health problem with increasing incidence, prevalence and mortality rates. Hypertension is one of the causes of kidney failure. So far there is no known research conducted regarding factors related to the prevalence of kidney failure. The aim of this study was to analyze various factors related to the incidence of chroni Chronic kidney failure is a global health problem with increasing incidence, prevalence and mortality rates. Hypertension is one of the causes of kidney failure. So far there is no known research conducted regarding factors related to the prevalence of kidney failure. The aim of this study was to analyze various factors related to the incidence of chronic kidney disease in hypertensive sufferers. This research method is descriptive analytical with a cross sectional approach, this research was conducted in the inpatient room of Prof Dr WZ Johannes Hospital in April-August 2023. The sample size was 100 respondents using consecutive sampling technique. Statistical tests are univariate, bivariate and multivariate. The result is that the relationship between age and kidney failure shows a p value = 0.129 > 0.05. relationship with gender p value = 0.687 > 0.05, relationship with blood pressure p value = 0.356 > 0.050, cholesterol level with p value = 0.374 < 0.05, relationship with LDL levels p value = 0.783 > 0.05, The relationship with HDL levels is p value = 0.096 > 0. Meanwhile, the education factor has a relationship with kidney failure with a p value = 0.002 < 0.05 and the treatment history factor has a relationship with p value = 0.356 > 0.050. The conclusion is that educational factors and treatment history are the dominant factors in controlling blood pressure, thus preventing the occurrence of complications of chronic kidney failure in hypertensive patients. c kidney disease in hypertensive sufferers. This research method is descriptive analytic with a cross sectional approach, the sample size is 100 respondents with a consecutive sampling technique. The results of statistical testing of the relationship between age and kidney failure show a p value = 0.129 > 0.05. relationship with gender p value = 0.687 > 0.05, relationship with blood pressure p value = 0.356 > 0.050, cholesterol level with p value = 0.374 < 0.05, relationship with LDL levels p value = 0.783 > 0.05, The relationship with HDL levels is p value = 0.096 > 0. Meanwhile, the education factor has a relationship with kidney failure with a p value = 0.002 < 0.05 and the treatment history factor has a relationship with p value = 0.356 > 0.050. The conclusion is that educational factors and treatment history are the dominant factors in controlling blood pressure, thus preventing the occurrence of complications of chronic kidney failure in hypertensive patients.